The effects of congested fixture periods on distance-based workload indices: A full-season study in professional soccer players - Clemente, F. M.; Silva, R.; Arslan, E.; Aquino, R.; Castillo, D.; Mendes, B. (Biology of Sport, 2021)
The aim of this study was to compare distance-based workload indices during congested fixture periods among different levels of participation in matches. Nineteen elite professional male players (age: 26.5 ± 4.3 years) from a European First League team were monitored daily over a full season using global positioning measurements. Distance-based measures (total distance, high-intensity running, high-speed running distance, and number of sprints) were collected daily. The following workload indices were calculated weekly: (i) acute load; (ii) acute : chronic workload ratio; (iii) training monotony; and (iv) training strain. During the season, seven congested weeks were selected. The participation levels of the players were categorized as starting in three matches (S3M), two matches (S2M), or one match (S1M) in the same week. Comparisons of the workload indices between levels of participation revealed that the acute load of total distance wassignificantly greater for S2M than S1M (+27%) and for S3M than for S1M (+30%). Moreover, the acute load of high-speed running was significantly greater for S2M than for S1M (+79%) and for S3M than for S1M (+60%). The acute load of high-intensity running was also significantly greater for S2M than for S1M (+54%) and for S3M than for S1M (+67%). This study revealed that acute load and training strain were meaningfully greater for S2M and S3M than S1M, although no significant differences were found between S1M, S2M, and S3M for the overall distance measures in terms of acute : chronic workload ratio and training monotony.